Photodynamic therapy of primary and recurrent forms of weakly pigment choroidal melanoma - K. P. Zhyliayeva; P. D. Demeshko; L. V. Navumenka; S. A. Krasny; D. A. Tzerkovsky; I. Yu. Zherko (Biomedical Photonics, 2022)
Treatment of poorly-pigmented tumors of small sizes can be carried out using photodynamic therapy (PDT). The material for the analysis was data on 112 patients. We used data from the Belarusian Cancer Registry, medical records of patients with clinically diagnosed choroid melanoma (C69.3 according to ICD-10) for the period 2013–2021. The size and level of blood flow in the tumors were assessed using an ultrasound machine with a doppler attachment. PDT was carried out using a «UPL PDT» semiconductor laser (Lemt, Republic of Belarus, λ=661 nm) with a light spot diameter of 1 to 3 mm for 60 s per field with a light dose of 50 J/cm2. The entire surface of the tumor was exposed to the action, with the fields “tiled”, from the periphery to the top of the tumor, with overlapping fields. Tumor pigmentation was assessed visually. To evaluate the treatment outcome, the general group of patients was divided into three subgroups according to thickness and basal diameter. Group I – 40 (35.7%) patients, with an average tumor thickness of 1.4±0.2 mm, basal diameter – 5.8±1.5 mm. II – 51 (45.5%) patients, with an average tumor thickness of 2.3 ± 0.3 mm, basal diameter – 7.9 ± 1.5 mm. III – 21 (18.8%) patients. The mean value of the tumor thickness was 3.8±0.4 mm, the basal diameter was 9.8±1.4 mm. After PDT in the general group (n=112), 29 (25.9%) patients had complete tumor resorption, and 83 (74.1%) patients had stabilization. The eyeball was saved in 107 (95.5%) patients. Continued growth and relapse were recorded in 34 patients: 25 (22.3%) and 9 (8.0%), respectively. In 29 (85.3%) patients, the eyeball was preserved after treatment of relapse and continued growth. 5 (4.5%) enucleations were performed. Adjusted one-year cumulative survival was 100%, 3-year and 5-year 95.8±2.4%, 93.7±3.1%, respectively